Mathematical and Computer Modeling of the State of Complex Systems under the Influence of Potential Forces (Global Journal of Computer Science and Technology, 2022)
This article considers the problem of determining critical points and areas in a system that is exposed to external forces As a result the system can lose its stability and go into a non-equilibrium state and then collapse and cause various kinds of catastrophes The study of the problem of identification and prediction of disasters is relevant because allows you to take preventive measures to prevent them and reduce the risks of various negative scenarios
Keywords: catastrophe; deformation; collapse; bifurcation; deformations; system stability